2013
DOI: 10.2174/1381612811319220010
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Bridging with Low Molecular Weight Heparins: A Systematic Review and Partial Meta-Analysis

Abstract: While the antithrombotic efficacy of bridging with LMWH has not been demonstrated, increased bleeding risk is observed in different types of surgery. PM/ICD surgery can be safely performed on continued VKA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 0 publications
1
11
0
5
Order By: Relevance
“…However, bridging was associated with an increased risk of major bleeding in five studies (OR, 3·60; 95% CI, 1·52–8·50). A further systematic review also concluded ‘while the antithrombotic efficacy of perioperative bridging with LMWH has not been demonstrated, increased bleeding risk is observed in different types of surgery’ (Eijgenraam et al , ).…”
Section: Warfarin and Other Vitamin K Antagonistsmentioning
confidence: 99%
“…However, bridging was associated with an increased risk of major bleeding in five studies (OR, 3·60; 95% CI, 1·52–8·50). A further systematic review also concluded ‘while the antithrombotic efficacy of perioperative bridging with LMWH has not been demonstrated, increased bleeding risk is observed in different types of surgery’ (Eijgenraam et al , ).…”
Section: Warfarin and Other Vitamin K Antagonistsmentioning
confidence: 99%
“…113 Because of heterogeneity in comparison groups, the authors limited the meta-analysis to studies on patients having pacemaker or implantable cardioverter defibrillator surgery. In the pooled analysis of six studies that compared patients who continued with a VKA during the procedure with those who received bridging therapy, the risk of bleeding complications was significantly increased with bridging therapy (relative risk 3.03, 1.86 to 4.95).…”
Section: Patients Taking Vkasmentioning
confidence: 99%
“…showed no significant difference in thrombotic rates (0.9% in bridged patients and 0.6% in non-bridged patients), but significantly increased bleeding rates (overall bleeding of 13.1% and major bleeding of 4.2% in bridged patients and 3.4%/0.9% in non-bridged patients, respectively) with an OR of 3.6 for major bleeding in bridged patients [6]. Another recent metaanalysis has shown similar results [4]. However, given the heterogeneity of individual studies and the underrepresentation of high-risk patients, it is possible that bridging is effective in the latter group.…”
Section: The Effectiveness Of Bridgingmentioning
confidence: 69%
“…The uncertainty is related to the lack of randomised controlled trials. There is increasing evidence from systematic reviews and meta-analyses that bridging therapy is associated with an increased risk of bleeding, Whilst the absolute reduction in thrombotic events is uncertain [4][5][6], and because of this various bridging therapy protocols are in use.…”
Section: Introductionmentioning
confidence: 99%